Correlation between Computer Workstation and Location of Musculoskeletal Disorders - Hafiz Ambyo Bagaskoro; Tertianto Prabowo; Setiawan Setiawan (Althea Medical Journal, 2016)
Background: The use of computer has been widely increased. This intensifies the risk of musculoskeletal disorders on long-term office workers. This study aims to find out the characteristics of musculoskeletal disorders in office workers with computer workstation which then lead to the presence or absence of the correlation between the two in order to avoid the pains endured.Methods: This was a cross-sectional study carried out from September–November 2014 in Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia. Seventeen samples were obtained from three different departments (finance and academics) by total sampling. The data was collected by validated questionnaire and it was analyzed by using simple linear regression method.Results: From 17 samples in total, 16 claimed that their workstation needs to be evaluated. Furthermore, the prevalent areas of musculoskeletal were shoulders (12 persons), lower back (10 persons), neck (9 persons), knee (9 persons), upper back (7 persons). The analysis using simple linear regression method showed no significant correlation between workstation characteristics and musculoskeletal disorders (p-value = 0.515).Conclusions: There is no correlation found between workstation characteristics and musculoskeletal disorders. [AMJ.2016;3(2):323–8]DOI: 10.15850/amj.v3n2.793